1976
DOI: 10.1177/030006057600400207
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment of the Therapeutic Efficiency of Antidepressant Agents

Abstract: A clinical trial of four weeks duration was conducted involving a total of thirty depressed patients, of both sexes, aged between twenty and thirty-four years. The total number of patients was divided into three groups of ten patients each. One group received amitriptyline, the second group was administered noxiptyline and the third group was given dibenzepine. All drugs were administered orally. Patients were submitted to psychometric testing before and after drug administration. The tests used included the '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Of these, 14 did not involve any measures that could be considered memory tests. However, it is noteworthy that one paper reported improvement in test performance in association with amitriptyline (Kupietz and Balka, 1976), and one no effect (Elwan et al, 1976) and the remainder reported detrimental effects of the drug (Landauer et al, 1969;Seppala et al, 1975;Seppala, 1977;Bye et al, 1978;Crome and Newman, 1978;Chan et al, 1980;Scott et al, 1982;Culig et al, 1983;Hindmarch et al, 1983;Linnoila et al, 1983;Hanks, 1984;Burns et al, 1986). Of the fifteen studies including memory tests (see Table l), nine involved administration to healthy volunteers ranging from 25 mg to 75 mg, all but one as a single dose.…”
Section: Amitriptylinementioning
confidence: 99%
“…Of these, 14 did not involve any measures that could be considered memory tests. However, it is noteworthy that one paper reported improvement in test performance in association with amitriptyline (Kupietz and Balka, 1976), and one no effect (Elwan et al, 1976) and the remainder reported detrimental effects of the drug (Landauer et al, 1969;Seppala et al, 1975;Seppala, 1977;Bye et al, 1978;Crome and Newman, 1978;Chan et al, 1980;Scott et al, 1982;Culig et al, 1983;Hindmarch et al, 1983;Linnoila et al, 1983;Hanks, 1984;Burns et al, 1986). Of the fifteen studies including memory tests (see Table l), nine involved administration to healthy volunteers ranging from 25 mg to 75 mg, all but one as a single dose.…”
Section: Amitriptylinementioning
confidence: 99%
“…Deficits in test scores, however, were recorded when alcohol was taken in addition; these impairments were greater than those observed following alcohol alone (Linnoila et al 1975). Four weeks of dibenzapine (240-480 mg/day) and 4 weeks of noxiptyline (150-300 mg/day) given to depressed patients did not interfere with their performance on a tracking test (Elwan et al 1976). Liljequist et al (1981) reported that maprotiline retarded the learning rate in some individuals on a paired associates learning test, and that the occurrence of such an effect was related to subjective reports of the degree of sedation experienced.…”
Section: Other Drugsmentioning
confidence: 99%
“…Only one study reviewed failed to detect any influence of this drug on psychological performance. Elwan et al (1976) prescribed 75-150 mg a day to 10 depressed patients for 4 weeks. This treatment regime did not significantly alter patients' performance on a tracking task, the authors' sole measure of mental function.…”
Section: Amitriptylinementioning
confidence: 99%
See 1 more Smart Citation